DIASPORA: OVERVIEW OF RESEARCH AND GEOPOLITICS - de Lame, Danielle (Revista Eletrônica: Tempo - Técnica - Território / Eletronic Magazine: Time - Technique - Territory, 2016)
I add, in this spontaneous passion that I see in many young Europeans, my academic conviction that serious studies in anthropology and history include, inevitably, a dimension of contact and networks that link people, often artificially bounded in the space necessary to administer and the convenience of research.